End-to-side Anastomosis on Digital Arteries: Just a Technical Choice or a Real Benefit?. Issue 9 (30th September 2022) - Troisi, Luigi; Tedone Clemente, Erica; Susca, Valentina; Vizcay, Macarena; Zanchetta, Francesco; Stucchi, Sara; Pajardi, Giorgio Eugenio
Abstract : Background: High-quality evidence is currently poor regarding the benefits of end-to-end (ETE) or end-to-side (ETS) anastomosis in arterial and venous anastomoses, despite being postulated as a potential influence on outcomes. A sufficient microvascular anastomosis is indispensable for the success of any free tissue transfer. ETS microvascular anastomoses have been becoming increasingly important as they allow reconstruction even in patients with impaired vascular status. To the authors' knowledge, no studies have examined the choice of ETE or ETS anastomoses specifically for digital arteries. Methods: We conducted a retrospective study of ETE and ETS anastomosis cases; the only inclusion criteria was that digital arteries (proper, common) were the recipient vessels. Results: Fifty-seven cases met the inclusion criteria. All the venous anastomoses were ETE. Of these cases, four total intraoperative complications (immediate thrombosis) and only one case of complete failure were registered. The ETE group consisted of 49 patients and the ETS group of eight patients. A comparison of the mean ischemia time in the two groups showed no statistically significant difference ( P = 0.121). Conclusions: We observed no difference in the reconstructive outcomes of hand free-flaps and reconstruction between ETE or ETS digital arteries anastomoses. The successful microsurgical reconstruction was independent of anastomotic technique. In particular, the results of our study demonstrated no statistically significant increase of the ischemia time; thus, no prolongation of operative time can be attributed to the higher technical challenge of the anastomosis.